2006
DOI: 10.1073/pnas.0608522103
|View full text |Cite
|
Sign up to set email alerts
|

Life-history evolution under a production constraint

Abstract: The recently formulated metabolic theory of ecology has profound implications for the evolution of life histories. Metabolic rate constrains the scaling of production with body mass, so that larger organisms have lower rates of production on a mass-specific basis than smaller ones. Here, we explore the implications of this constraint for life-history evolution. We show that for a range of very simple life histories, Darwinian fitness is equal to birth rate minus death rate. So, natural selection maximizes birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
136
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(139 citation statements)
references
References 27 publications
2
136
1
Order By: Relevance
“…The relationship was linear, which is consistent with Fenchel and Finlay's (1983) observation that production is linearly related to metabolic rate in protists. As expected, as metabolism fuels production (Brown and Sibly, 2006), individuals had the highest metabolic rates and highest division rates at low densities. Our estimated death rate function indicated that deaths were negligible until metabolic rates were highly suppressed (Figure 3).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The relationship was linear, which is consistent with Fenchel and Finlay's (1983) observation that production is linearly related to metabolic rate in protists. As expected, as metabolism fuels production (Brown and Sibly, 2006), individuals had the highest metabolic rates and highest division rates at low densities. Our estimated death rate function indicated that deaths were negligible until metabolic rates were highly suppressed (Figure 3).…”
Section: Discussionmentioning
confidence: 69%
“…From the point of view of population regulation, variation in resource supply should lead to altered metabolic rates and changes in the allocation of energy and resources to growth, reproduction or survival, driving changes in population growth rate (Tonn et al, 1994;Lewis et al, 2001;Schmoker and Hernandez-Leon, 2003;Forrester et al, 2006). As metabolism fuels production (Brown and Sibly, 2006), a reduction in metabolic rate should decrease the rate at which offspring can be produced. Similarly, survival should be enhanced when metabolism can be allocated to cell maintenance or other defense mechanisms, such as avoidance of predation.…”
Section: Introductionmentioning
confidence: 99%
“…The differential of the profile (ri/wifalse|wi=w=1/wc) at the limit of the average variant ( w ) is the selection gradient (Figure 1b) that describes selection as a function of the average body mass. And the evolutionary equilibrium (w=1/c) is the optimum of the selection integral [italic∂rifalse/italic∂wi|wi=wdw; Figure 1c] that integrates the selection gradient across the potential evolution in the average mass of the population.The more recent approach of metabolic ecology (Brown & Sibly, 2006) assumes, somewhat contrary to evidence, that the variation in the intraspecific birth rate (biwi1/4) follows the interspecific allometry for biotic periods, with an intraspecific birth rate that declines with mass instead of increasing as often observed. Large species may then evolve by a survival rate that increases with mass.…”
Section: Physiological Selection On Massmentioning
confidence: 98%
“…The more recent approach of metabolic ecology (Brown & Sibly, 2006) assumes, somewhat contrary to evidence, that the variation in the intraspecific birth rate (biwi1/4) follows the interspecific allometry for biotic periods, with an intraspecific birth rate that declines with mass instead of increasing as often observed. Large species may then evolve by a survival rate that increases with mass.…”
Section: Physiological Selection On Massmentioning
confidence: 98%
“…Compared to large-bodied animals, small-bodied animals often have shorter life spans and lower antibodybased adaptive immunity but greater metabolic, developmental, and reproduction rates (Sheldon and Verhulst 1996;Ricklefs and Wikelski 2002;Brown et al 2004;Brown and Sibly 2006;Lee 2006;Lee et al 2008;Johnson et al 2012). Plants fall along a similar continuum based on traits of their leaves (Reich 2001;Enquist et al 2007;Cronin et al 2010b).…”
Section: Introductionmentioning
confidence: 99%